Frugal Design in Practice: From theory to increased biosafety in tuberculosis laboratories in Peru - Wingren Bergman, Carl; Eliasson, Filip (My University, 2023)
This thesis has examined Frugal Design (FD), both in theory and practice, to grant a deeper understanding of how to implement the approach. The research included a literature review and a case study, with a focus on developing a Frugal Design biosafety enclosure for TB laboratories in Peru that currently lack this necessary piece of equipment. The main goal of the thesis has been to answer two research questions: What is Frugal Design? How can it be utilised by designers? Research through design has been the method of this thesis. It was initiated with a literature review based on a structured database search for "frugal design". The proposed definitions and methods from the literature study were then applied in a product development project covering the design of a biosafety enclosure. In this manner the FD approach has been tested in practice to draw conclusions about its implementation. Results from the theoretical and practical work have been used to analyse the FD approach in terms of definitions, methods, possible tools, and its utility. The research generated two main findings: A new design of a Frugal ventilated workstation that is easy to produce and implement in laboratories in need of a biosafety enclosure, in Lima and other parts of Peru. A new proposed Frugal Design framework defining FD using seven FD factors and a number of tools to achieve these factors. Further more a model of the FD process including several FD process elements, that explain what a designer can do to best use FD principals and to create FD designs